Tocopherol polyethylene glycol succinate-modified hollow silver nanoparticles for combating bacteria-resistance. (10th April 2019) - Kang, Xu-Qi; Qiao, Yue; Lu, Xiao-Yang; Jiang, Sai-Ping; Li, Wei-Shuo; Wang, Xiao-Juan; Xu, Xiao-Ling; Qi, Jing; Xiao, Yong-Hong; Du, Yong-Zhong
Abstract : TPGS capped AgNPs could cross the bacterial cell wall and inhibit the activity of efflux pumps, eventually antagonize drug-resistance in the acute peritonitis model mice effectively. Abstract : Multiple drug resistance and the increase in the appearance of superbugs together with the exceedingly scant development of new potent antibiotic drugs pose an urgent global medical threat and imminent public security crisis. In the present study, we fabricated well-dispersed tocopherol polyethylene glycol succinate (TPGS)-capped silver nanoparticles (AgNPs) of about 10 nm in size. The hollow structure of the TPGS-capped AgNPs (TPGS/AgNPs) was confirmed and applied to load antibiotics. The TPGS/AgNPs proved to be able to cross the bacterial cell wall and penetrate into bacteria, thereby delivering more of the antibiotic to the interior of bacteria and thus enhancing the in vitro antibacterial effect of the antibiotic, even overcoming the drug-resistance in drug-resistant E. coli and Acinetobacter baumannii . It was found that the TPGS modification in the TPGS/AgNPs could decrease the activity of the efflux pumps AdeABC and AdeIJK in drug-resistant Acinetobacter baumannii via inhibiting the efflux pump genes adeB and adeJ, thus increasing the accumulation of the delivered antibiotic and overcoming the drug-resistance. Tigecycline delivered by TPGS/AgNPs could effectively antagonize drug-resistance in an acute peritonitis model mice, thereby increasing the survival rate and alleviating the inflammatory response. TPGS/AgNPs were developed as a novel and effective antibiotic delivery system and TPGS was demonstrated to have great potential as a pharmaceutical excipient for use in drug-resistant infection therapy.